2020
DOI: 10.1093/cid/ciaa259
|View full text |Cite
|
Sign up to set email alerts
|

The Integrase Inhibitors Dolutegravir and Raltegravir Exert Proadipogenic and Profibrotic Effects and Induce Insulin Resistance in Human/Simian Adipose Tissue and Human Adipocytes

Abstract: Background Although some integrase strand transfer inhibitors (INSTIs) promote peripheral and central adipose tissue/weight gain in people with human immunodeficiency virus (PHIV), the underlying mechanism has not been identified. Here, we used human and simian models to assess the impact of INSTIs on adipose tissue phenotype and function. Methods Adipocyte size and fibrosis were determined in biopsies of subcutaneous and vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
108
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 35 publications
6
108
1
Order By: Relevance
“…Several studies reported a higher level of fibrosis in adipose tissue of ART-treated HIV-infected patients compared to noninfected subjects [6,7,9]. Finally, integrase inhibitors (INSTIs), a recent widely used class of ART, have less impact on senescence of endothelial cells together with anti-inflammatory properties [58,59] but their use is associated with fat gain and higher AT fibrosis [60][61][62][63]). Taken as a whole, ART can also have a role in adipose tissue aging in HIV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a higher level of fibrosis in adipose tissue of ART-treated HIV-infected patients compared to noninfected subjects [6,7,9]. Finally, integrase inhibitors (INSTIs), a recent widely used class of ART, have less impact on senescence of endothelial cells together with anti-inflammatory properties [58,59] but their use is associated with fat gain and higher AT fibrosis [60][61][62][63]). Taken as a whole, ART can also have a role in adipose tissue aging in HIV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed in compliance with the principles of the Declaration of Helsinki, and was approved by the local independent ethics committee. The ASCs were isolated using a collagenase (Roche Diagnostics, Basel, Switzerland) digestion technique, as described previously (Gorwood, Bourgeois et al 2019, Gorwood, Ejlalmanesh et al 2020), after seeding in Eagle’s Minimum Essential Medium alpha (Thermo Fisher Scientific, Courtaboeuf, France) supplemented with 10% foetal bovine serum (FBS) (PAN-Biotech, Aidenbach, Germany), 2 mmol/L glutamine, 100 U/mL penicillin/streptomycin, 10 mmol/L HEPES (Thermo Fisher Scientific), and 2.5 ng/mL FGF2 (PeproTech, Rocky Hill, NJ, USA). Upon confluence, adherent cells were trypsinized (Thermo Fisher Scientific) and seeded at a density of between 2000 and 4000 cells/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Differentiation of ASCs was induced by the addition of proadipogenic Dulbecco Modified Eagle’s Medium (DMEM), 4.5 g/L glucose (Thermo Fisher Scientific), 10% FBS, 2 mmol/L glutamine, 100 U/mL penicillin/streptomycin, 10 mmol/L HEPES, 1 μmol/L dexamethasone, 250 μmol/L 3-Isobutyl-1-methylxanthine (IBMX), 1 μmol/L rosiglitazone, 1 μmol/L insulin (Merck, Sigma-Aldrich) for 5 days, and then maintained in DMEM with rosiglitazone and insulin up until day 14. Cells were then stained for Oil-Red-O (Merck, Sigma-Aldrich) and quantified at 520nm as described previously (Gorwood, Bourgeois et al 2019, Gorwood, Ejlalmanesh et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations